The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s13138-020-00177-w
|View full text |Cite
|
Sign up to set email alerts
|

First Year Students’ Resilience to Cope with Mathematics Exercises in the University Mathematics Studies

Abstract: University mathematics studies are known for high dropout especially in the freshmen year. This dropout is often traced back to the excessive demands freshmen have to face. Research aimed at identifying students’ characteristics that enable them to overcome the demands, for example through cognitive abilities, motivational constructs or self-beliefs. In this paper, we take a different perspective and suggest to include a construct that has not been considered in university mathematics education so far: mathema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 81 publications
0
2
0
1
Order By: Relevance
“…It is well known that undergraduate mathematics students are exposed to serious challenges in their early years of study (e.g. Hoyles, Newman, and Noss 2001;Neumann, Jeschke, and Heinze 2020;Rach and Heinze 2017). Given that mathematics teacher students (as in our sample) typically take the same mathematics courses as the mere mathematics majors, teacher students likely experience the same challenges as well.…”
Section: Discussionmentioning
confidence: 98%
“…It is well known that undergraduate mathematics students are exposed to serious challenges in their early years of study (e.g. Hoyles, Newman, and Noss 2001;Neumann, Jeschke, and Heinze 2020;Rach and Heinze 2017). Given that mathematics teacher students (as in our sample) typically take the same mathematics courses as the mere mathematics majors, teacher students likely experience the same challenges as well.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, the well-known general negative effect of mathematics as a second subject might have become visible here. The high complexity associated with a university degree in mathematics regularly leads to students being overwhelmed and sometimes even dropping out of their studies (Hoyles et al, 2001 ; Neumann et al, 2021a ). For teacher education in particular, studies have reported negative effects of mathematics as a second subject on the development of pre-service teachers' professional competence (even for competence aspects related to the subject studied besides mathematics; e.g., Neumann et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…The research findings highlight the critical role of different stakeholders, particularly teachers, in promoting MR. Studies by various researchers (Baker et al, 2019;Muntazhimah & Ulfah, 2020;Neumann et al, 2021) emphasize the importance of targeted recommendations for teachers in enhancing MR in educational settings. These recommendations stress the need for teachers to be aware of the affective, cognitive, and pedagogical aspects of MR (Atahan & Akyüz, 2020;Johnston-Wilder et al, 2021).…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%